The Effect of Jajar Legowo Planting System on Ciherang Paddy Varieties - Darwati Susilastuti; Aditiameri Aditiameri; Ubuh Buchori (AGRITROPICA : Journal of Agricultural Sciences, 2018)
Intensification on paddy is done one of them by setting the spacing. This study aims to examine the effect of spacing system on growth and paddy production. The research was conducted in Bojongmangu Village, Bekasi Regency, West Java Province. The study used an experimental method  Randomized Completely Block Design (RCBD) with 1 factor that is   planting system, namely tegel  system 20 cm x 20 cm, tegel system  25 cm x 25 cm , jajar legowo 2:1 (25x12,5x50 ) cm, jajar legowo 4:1 full (25 x12,5x50 ) cm, jajar legowo 4:1 free space (25 x12,5x50 ) cm, and jajar legowo 6:1 (25x12,5x 50) cm. Each treatment is repeated   3 times. The results showed that jajar legowo planting system 2:1 gives the number of panicles per clump, number of grains per panicle, weight of 1000 grains and the average yield per hectare is highest, followed by jajar legowo 4:1 full planting systemKeywords: Jajar Legowo, Planting System